2013
DOI: 10.1021/cs400939p
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis Catalysis of Miscanthus Xylan to Xylose Using Weak-Acid Surface Sites

Abstract: Adsorption and hydrolysis of xylan polysaccharides extracted from Miscanthus biomass are demonstrated, using surface-functionalized MCN (mesoporous carbon nanoparticle) materials that comprise weak-acid sites, at a pH corresponding to biomass extract. Extracted xylan polysaccharides consist of a peak molecular weight of 2008 g/mol according to GPC (gel-permeation chromatography), corresponding to approximately 15 xylose repeat units, and, a calculated length of 7 nm and radius of gyration of 2.0 nm based on mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 30 publications
8
79
0
1
Order By: Relevance
“…In this reaction, the strongly acidic property of HSO 3 -MSN was useful, unlike weak-acid surface sites of porous materials that act as suitable candidates for biopolymer chain-breaking. [10,11] The very purpose of utilizing the ionic liquid [BMIM]Cl for the pre-treatment of cellulose is to disrupt the interactions between hydrogenbonded sheets in cellulose and solvation of microfibrils consisting of a large number of glucan chains, which is possible via disruption mechanism by [BMIM]Cl. [12(a)] In this case, nucleophilic imidazole can attack and disrupt the hydrogen bonds in cellulose by converting to a mixture of modified cellulose and amorphous cellulose among which later is more prone to enzymatic hydrolysis.…”
mentioning
confidence: 99%
“…In this reaction, the strongly acidic property of HSO 3 -MSN was useful, unlike weak-acid surface sites of porous materials that act as suitable candidates for biopolymer chain-breaking. [10,11] The very purpose of utilizing the ionic liquid [BMIM]Cl for the pre-treatment of cellulose is to disrupt the interactions between hydrogenbonded sheets in cellulose and solvation of microfibrils consisting of a large number of glucan chains, which is possible via disruption mechanism by [BMIM]Cl. [12(a)] In this case, nucleophilic imidazole can attack and disrupt the hydrogen bonds in cellulose by converting to a mixture of modified cellulose and amorphous cellulose among which later is more prone to enzymatic hydrolysis.…”
mentioning
confidence: 99%
“…It was also found that the activity of K26 decreased by reducing the amount of oxygenated groups. We and Chung et al, respectively, showed that the catalytic activity of such carbons was maintained after treating the materials with sodium acetate/acetic acid buffer of pH 4.0-4.1 [ 14 ]. If the carbon catalysts were strong acids, they would be deactivated by the treatment due to ion exchange with Na + .…”
Section: Catalytic Activities Of Carbonsmentioning
confidence: 99%
“…However, weak acids may also be useful, as cellulase enzymes selectively hydrolyze cellulose using weak acids/bases [ 13 ]. Moreover, weak acids can survive in the presence of salts potentially derived from biomass, whereas solid strong acids readily cause cation exchange, namely, proton leaching [ 14 ]. Solid weak acids are worthwhile to investigate for the hydrolysis of cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonated CMK-3 was used for the hydrolysis of cellulose and achieved a high cellulose conversion of 94.4% and glucose yield of 74.5% [49]. More recently, Chung et al used MCM-48 nanoparticles prepared with a modified Stöber method as a template to synthesize sulfonated mesoporous carbon nanoparticles (HSO3-MCN) [84,85].…”
Section: Thermal Carbonizationmentioning
confidence: 99%
“…For example, benzene sulfonic acid degraded in water at 160 (Fig. 7) [85]. To synthesize this weak acid catalyst, HSO3-MCN was treated in water at 200 °C in order for a fraction of the sulfonic acid sites to leach.…”
Section: Thermal Carbonizationmentioning
confidence: 99%